Comparison the effect of two types of light curing units with different modes on microleakage of composite filling in Cl II restorations - Esmail Yassini; Mansoureh Mirzaei; Bahar Safaei Yazdi; Zohreh Moradi (Tehran University of Medical Sciences, 2017)
Background and Aims: One of the main disadvantages of light cured composite resin materials is polymerization shrinkage upon curing. This leads to the microleakage of restoration and finally failure of the restoration. The purpose of this study was to investigate the effect of two types of light curing devices with different modes on the microleakage of posterior composite filling in Cl II restorations. Materials and Methods: In this experimental study, 30 extracted sound molar human teeth were collected. All specimens were randomly divided into 3 groups of ten: Standard LED irradiation, pulse curing LED irradiation and QTH irradiation. All samples were prepared with mesial and distal boxes and composite fillings were done with three different light curing patterns for 20 s. After thermocycling, the specimens were kept in 2% methylene Blue solution for 24 h for microleakage test. After sectioning, the samples were evaluated by a stereomicroscope. For data analysis one-way ANOVA and Kolmogorov-Smirnov were used. P<0.05 was considered statistically significant. Results: The quantitative tests showed that there were no statistical difference between study groups (P>0.05). Conclusion: The results showed that both light curing devices were effective and no significant difference between different modes of LED light curing device on microleakage of class II composite restorations was found.